The ENS Collection: a systematic study of brachiopods from the Lower Permian Vøringen Member, Kapp Starostin Formation, Spitsbergen. - L. Angiolini; S. L. Long (2008)
Twenty-two species from nineteen brachiopod genera are described. They represent a collection of Permian brachiopods housed at the Natural History Museum of London and collected by the joint English, Norwegian and Swedish (ENS) Expedition in 1939 at Skansen (Billefjorden, Spitsbergen) from the Vøringen Member of the Kapp Starostin Formation. The generic position of many species erected at the end of the eighteenth century and at the beginning of the nineteenth century are addressed and discussed and two new genera, Archboldevia n. gen. and Bruntonia n. gen, are erected. The former is represented by Archboldevia impressa (Toula, 1875) and differs from the allied genus Yakovlevia Fredericks, 1925 by its non geniculate valves, large ears, the absence of auricular spines and of symmetrically placed thick ventral spines, and by its ventral musculature. The second, with type species Bruntonia maynci (Dunbar, 1955), is erected to include arctic species very similar to Horridonia Chao, 1927, but lacking ventral hinge spines and showing different dorsal internal characters. The brachiopods of the ENS collection suggest a late Artinskian to Kungurian age for the Vøringen Member; they strongly correlate with coeval fauna from Central Alaska, the Canadian Arctic, northeast Greenland, Pechora and the Urals in Russia.